Prototype of a Coupling Device to Investigate Focused Ultrasound-Induced Inertial Cavitation for Drug Delivery Applications - George Benedikt; Wittenbrink Michel; Savšek Ula; Kroh Christian; Fischer Dagmar; Ermert Helmut; Rupitsch Stefan J. (Current Directions in Biomedical Engineering, 2023)
Focused ultrasound (FUS) can be used as a drug delivery application for localized chemotherapy to treat cancer. The effect of ultrasound-induced inertial cavitation is promising to trigger drug release from nanocarriers. To investigate this effect, usually, a passive cavitation detection setup is employed. However, applying such a setup is challenging for in vivo experiments, as the test object may need to be fixed inside the water tank. Thus, we present a prototype of a coupling device that could significantly simplify experiments. Since this setup favors undesired sound wave interference and their resulting exceedance of the Mechanical Index, we additionally investigated different signal lengths. The occurrence of standing waves at a signal length of 44 cycles can both be derived from a changing cavitation activity and our calculations. The appearing interference also results in a mean increase of the cavitation activity by ≈ 5.1 %, verified by our experiments as well.